Petrography and geochemistry of siliciclastic sediments in Permo-Triassic transition from the southern Pranhita-Godavari Gondwana basin, India: Implications for paleoclimate - Sampa Ghosh (Journal of Asian Earth Sciences: X, 2023)
The Kamthi Formation, in the intracratonic Pranhita-Godavari Gondwana rift basin, bore signatures of climate change from a warm humid climate in Late Permian to hot arid during the Early Triassic. Sedimentation took place mainly under fluvial conditions. The Kamthi sediments were unaffected by burial diagenesis and the source remained the same, therefore this provides an excellent opportunity to study the climatic influence on petrogenesis in an intracratonic rift basin. Subsurface palynofacies data of Kamthi Formation from the southern part of the basin established the presence of Upper Permian rock units equivalent to the Raniganj Formation, which are overlain by Lower Triassic sediments equivalent to Panchet Formation of the Damodar valley Gondwana basins, and are separated by a gradational contact. QFL and trace element compositions reveal transitional continental to craton interior provenance with dominantly felsic source areas, along with some meta-sedimentary and mafic components. Dominance of kaolinite, coal, alteration of K-feldspar, and biotite in the Raniganj equivalent sandstones attests to a humid climate. The presence of mostly fresh K-feldspar, ferruginous matrices, Fe-carbonate nodules, cutans, and microcrystalline silica cement in the Panchet equivalent sandstones mark a shift from humid to arid/semi-arid. This climatic shift is not reflected in the uniform feldspatho-quartzose to quartzose sandstone compositions and mudstone major oxide compositions. The mudstones are depleted in mobile elements, have low K2O/Al2O3 (0.11–0.18), low ICV (0.35–0.72), high SiO2/Al2O3 (2.3–3.4), high K2O/Na2O and moderately high CIA (80.12–87.05) that collectively suggest moderately intense weathering. Despite the humid climate, the Raniganj Formation equivalent rock units did not attain the highest mineralogical maturity due to proximity to relatively high-relief source areas in a fluviolacustrine environment. This relationship resulted in a lack of short-term sediment storage that favoured rapid erosion and sedimentation.